Pkm Pelatihan Membuat Abon Cabe Bagi Siswa Berkebutuhan Khusus Di SLB Negeri Polewali Mandar - Sulasminah, Dwiyatmi; Usman, Usman; Hadi, Purwaka; Bastiana, Bastiana; Meidina, Tatiana; Kasmawati, St.; Saleh, Wizerti Ariestuti; Mappincara, A. (Civic Education Law and Humaniora : Jurnal Pengabdian Masyarakat Terintegrasi, 2023)
The Community Partnership Program (PKM) partner is Polewali State SLB. The problems are: (1) the lack of knowledge and skills of students with special needs for independent living after they graduate from school. (2) students with special needs need to be given skills for their independent lives in society in the future, (3) it is necessary to design a simple vocational skills program by schools so that students with special needs gain social and economic independence, (4) students with special needs in Polewali state SLB have not once given the skill of making shredded chilies. The external target is students with special needs to have independence both socially and economically through training in making shredded chilies. The methods used are: lectures, demonstrations, questions and answers, with partners. The results achieved are (1) partners have knowledge and skills in independent life, (2) partners acquire simple life skills. (3) partners get information about vocational skills programs for students with special needs, (4) students get knowledge and skills in making shredded chilies, (5) the skills that have been given inspire schools to teach skills in making shredded chilies to culinary skills